PERANCANGAN UI/UX APLIKASI CRYPTOCURRENCY WALLET BERBASIS ANDROID MENGGUNAKAN HEURISTIC EVALUATION DAN SYSTEM USABILITY SCALE - Attaqwa, Qevin; Junadhi, Junadhi; Andesa, Khusaeri; Kudadiri, Parlindungan (Universitas Dharmawangsa, 2026)
The development of blockchain and cryptocurrency technology has increased the need for cryptocurrency wallet applications that are not only secure but also easy to use for a wide range of users. However, the complexity of features and technical terms in digital financial applications often causes difficulties for users, especially beginners, so usability-oriented UI/UX design is needed. This study aims to design and evaluate the UI/UX of an Android-based cryptocurrency wallet application using the Design Sprint approach and the Heuristic Evaluation and System Usability Scale (SUS) methods. The design process is carried out through the stages of understanding the problem, sketching a solution, determining the best design, building a prototype, and conducting testing. The resulting prototype is then evaluated using Heuristic Evaluation based on Nielsen's ten principles to identify usability issues. The evaluation results indicate several improvements that need to be made in the aspects of system status clarity, display consistency, and prevention of user errors. After refining the design, the prototype was tested with users using the SUS questionnaire. Based on the results of testing on 5 respondents, the average SUS score was 78.4, which is included in the acceptable category and is at the good usability level. These results indicate that the application has a good level of ease of use, clear navigation, and is able to provide a positive user experience. Thus, the application of Design Sprint in the design process, combined with Heuristic Evaluation and SUS, proved effective in producing intuitive, informative, and user-oriented UI/UX designs for cryptocurrency wallet applications. This research is expected to serve as a reference in the development of more user-friendly mobile-based digital financial applications.